The “great party of the proletarian youth”: theory and practice of the counterculture according to the review Re Nudo (1970-1976) (Quinto Sol, 2024)
The article analyzes the experience of the Italian countercultural magazine Re Nudo, during the years 1970-1976. The research highlights the important presence of the magazine at the national level and summarizes its main positions. Focusing on the publication's openness to feminist and gay groups and its search to politicize the sphere of popular youth music, the article underscores the magazine's attempt to stimulate a cultural renewal in political activism. The analysis highlights the complexities of this project, taking stock of the limits and open possibilities in Italy in the 1970s
Keywords: counterculture; youth; gender; sexuality